ON THE ORIGIN OF LUNAR MATERIAL - Galimov E.M. (My University, 2004)
Under certain conditions the formation of the Moon from a primary material similar in composition to CI chondrites can meet the well-known geochemical criteria, including the deficit of iron in the Moon, its depletion in volatiles, the observed proportions of siderophile elements, and Hf-W systematics. The necessary conditions can be attained in the model of planetary body formation from a collapsing cloud of hot particles. This model is fundamentally different from the universally accepted mechanism of planet accumulation through the collision of solid planetesimals and requires a comprehensive analysis of its dynamical plausibility. The choice between the proposed model and the giant impact hypothesis will be facilitated by the measurement of the size of the lunar core by direct seismic methods during planned cosmic studies on the lunar surface.